The Conjunctival Flora In Vernal Conjunctivitis Patients - Guenduez, Abuzer; Guenduez, Ayten; Cumurcu, Tongabay; Doganay, Veysel; Seyrek, Adnan (Amer Soc Contemporary Medicine Surgery & Ophthalmology, 2009)
We investigated conjunctival flora changes in vernal conjunctivitis (VC) (n = 30) patients compared to the normal eye (n = 30). Growth was observed in 86.6% of the vernal group, and 80% of the control group specimens. We believe that administering prophylactic treatment would be helpful in VC patients who are to have intraocular surgery to prevent postoperative endophthalmitis.
Keywords: Bacterial-Flora; Keratoconjunctivitis; Epithelium; Challenge